Fatigue analysis of steering rack and pinion system - Sean, Kendrick Soh; Adam, A. M.; Mohd Akramin, Mohd Romlay; Mohd Shamil, Shaari (Institution of Engineering and Technology, 2022)
The steering rack and pinion systems are widely used in the automotive industry today due to their simplicity, compactness, and dependability. The primary goal of this paper is to investigate the fatigue of the steering rack and pinion system. In this paper, we analyzed two components in the steering system that are connected to each other. Firstly, this paper investigates the suitable material with proper boundary conditions for the model. Next, the contact of stresses between two mating gears of both the steering rack and pinion system must be determined. To pinpoint and observe the total deformation of the model design during simulation using ANSYS software. Lastly, in this paper, we must identify and discuss the life cycle and safety factor for the steering rack and pinion system model using a fatigue tool package. The ANSYS software results are presented and discussed to ensure that all objectives have been met successfully. The implementation via simulation results and mathematical calculations in research will improve the performance and efficiency of a design or model.